Pengaruh Kepuasan Kerja dan Kompensasi terhadap Kinerja Karyawan : Studi Kasus pada Showroom Hebo Car - Nabila Indah Safitri; Cahyadi Husadha; Tutiek Yoganingsih (Jurnal Riset dan Inovasi Manajemen, 2024)
This study aims to determine whether Job Satisfaction and Compensation can affect Employee Performance at the Hebo Car Showroom. The method used in this study is a quantitative method. The sample used was 40 respondents and focused on Hebo Car Showroom employees. The sampling technique used a saturated sampling technique. The data collection technique used a questionnaire. The data analysis technique used a statistical method with SmartPLS 3.0 Software. The results of this study indicate that: 1) Job Satisfaction has a positive and significant effect on Employee Performance, 2) Compensation has a positive and significant effect on Employee Performance, and 3) Job Satisfaction and Compensation have a simultaneous effect on Employee Performance.